Nutrient and Heavy Metal Contents of Meretrix sp. from Bancaran Estuary, Indonesia - Ambarwati Reni; Purnomo Tarzan; Fitrihidajati Herlina; Rachmadiarti Fida; Anggorowati Rahayu Dwi (MATEC Web of Conferences, 2022)
People in South East Asia region have consumed hard clam for a long time. This clam also actively collected and traded by local people around beaches and estuaries in Indonesia. The purposes of this research were to analyze protein and content of hard clam (Meretrix sp.) collected from Bancaran Estuary, Indonesia and to evaluate the content of lead (Pb) and cadmium (Cd). The sample of clams was collected by hand picking during low tide. Fresh samples of clams were kept in a cool box. Fresh samples of the flesh were taken for analysis of nutrient and heavy metal content as well. The content of fat was analyzed using soxhlet method; meanwhile the protein content was analyzed using Kjeldahl method. In addition, the content of cadmium (Cd) and lead (Pb) in the flesh of hard clam were tested using atomic adsorption spectroscopy. The results indicated of the flesh of hard clam contained fat and protein, namely 3.25±0.42% and 10.26±0.46% respectively. Meanwhile, the content of Cadmium (Cd) and Lead (Pb) were 0.0306±0.0053 ppm and 0.0458±0.0035 ppm respectively. The level of Cd and Pb were lower than the level of maximum acceptable limit. Therefore, it can be concluded that the flesh of hard clam was safe for consumption.